Logística reversa automotiva: o fluxo de baterias como indicador de prática cultural sustentável na cidade de São Luís – Maranhão - SILVA, Vanessa Leite da (2022)
Environmental protection requires a large diversity of social actions addressed to decrease the problems caused directly and indirectly by production, circulation, and consumption activities, conspicuously those that generate a risk of contamination of natural resources appropriated by society. This is an exploratory, descriptive, and interdisciplinary field research with a qualitative approach on the reverse logistics of vehicular batteries in São Luís. This research aims to know the practice of the reverse flow of automotive batteries in São Luís - Maranhão, through the perception of the socio-environmental and economic bias. The methodology adopted involves the data collection and analysis of information obtained from secondary and primary sources as publications, obtained by field research and application of semi-structured interviews with professionals from stores, junkyards, and vehicle owners regard to the tasks collection, reuse, and sale of automotive batteries. Due to the social distancing caused by COVID-19, some interviews were performed by phone or videoconference. The relevance of the research is based on the little importance attributed to the studies of this sustainable commercial practice and the possibility of developing new lines of investigation that can sensitize society to this theme, additionally the possibility of contributing to the scientific framework on the subject and establish bases for future studies aiming to improve the environmental quality and people's lives. The motivational factors that support this commercial practice are discussed, besides the perception of traders, vehicle owners, and manufacturers in this dynamic market for the commercialization of vehicular batteries, as well as the steps and particularities present in the reverse flow of use of these batteries. It was found that the specific legislation for disposal of solid waste, has a strong influence on the frequency and the way in which the reverse logistics of vehicular batteries occurs in the commercial region of São Luís.